The effects and challenges of the South African Cuban Technical Support Program (SACTSP) in the South African Human Settlements Sector - Mukhadakhomu, A.; Khumalo, P. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The aim of the paper is to evaluate the effectiveness of the South African Cuban Technical Support Program (SACTSP) as is currently applied in the participating provincial Departments of Human Settlements (Mpumalanga, Western Cape, Limpopo and Free StateThe post-apartheid government inherited an urban housing backlog of approximately 1.3 million units at its inception in 1994. This huge backlog was partially contributed by apartheid discriminatory administrations and laws such as the Black (Native) Laws Amendment Act, No 46 of 1937 and the Black Communities Development Act, No 4 of 1984 along with rapid urbanization during the post-apartheid period. In a bid to address past injustice related to housing, it has become necessary for the post-apartheid government to diversify housing delivery approach to include alternative development and delivery strategies, methodologies and products including upgrading of informal settlements, and implementation of People Housing Process (PHP). Amongst other adopted methodology for fast tracking housing service delivery was the South African Cuban Technical Support Programme (SACTSP). The SACTSP is governed by the bilateral agreement and is aimed at recruiting the Cuban Technical Advisors to South Africa to assist in the delivery of sustainable human settlements. Keywords: Cuban technical advisors, Evaluation, Human settlements, South African Cuban technical support program, Sustainable human settlements
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Cuban technical advisors; Evaluation; Human settlements; South African Cuban technical support program; Sustainable human settlements; Human settlements; Housing